Procedure for Regional Property Removal at Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kabupaten Serang - Siti Agustina Rahayu (PT. EQUATOR SINAR AKADEMIA, 2021)
The objectives of this study are: to find out the procedure for the elimination of Regional Property (BMD) at the Regional Financial and Asset Management Agency (BPKAD) Serang Regency, to find out what obstacles occur in the implementation of the elimination of Regional Property (BMD) at the Regional Asset Management Agency. Regional Finance and Assets (BPKAD) Serang Regency. The results of the study indicate that the abolition of State Property has been carried out according to the procedures and the obstacles faced and overcome.